Comparison of Photocatalytic Performance of Degussa TiO2 P25 and P90 in Gas Phase Photocatalytic Reactor - Il In, Su (Asian Journal of Chemistry, 2011)
Photocatalytic performances of Degussa TiO2 P25, one of the most active commercial photocatalysts and P90, recently developed material by Degussa, were studied using gas phase photocatalytic reactor. Photodecomposition of methyl tert-butyl ether was used to characterize photocatalytic behaviour of two samples containing different ratio of TiO2 anatase and rutile. This is the first demonstration that although the activity of P90 was higher than that of P25 TiO2, the surface area normalized activity showed that P25 had a better performance.